2008
DOI: 10.1523/jneurosci.0338-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Transducin γ-Subunit Sets Expression Levels of α- and β-Subunits and Is Crucial for Rod Viability

Abstract: Transducin is a prototypic heterotrimeric G-protein mediating visual signaling in vertebrate photoreceptor cells. Despite its central role in phototransduction, little is known about the mechanisms that regulate its expression and maintain approximately stoichiometric levels of the ␣-and ␤␥-subunits. Here we demonstrate that the knock-out of transducin ␥-subunit leads to a major downregulation of both ␣-and ␤-subunit proteins, despite nearly normal levels of the corresponding transcripts, and fairly rapid phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
106
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(122 citation statements)
references
References 53 publications
14
106
2
Order By: Relevance
“…Previous work by us and others (10,11) showed that Gγ 1 knockout results in progressive photoreceptor loss. Even before degeneration begins, affected rods sustain a >90% loss of other transducin subunits: Gα t and Gβ 1 .…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…Previous work by us and others (10,11) showed that Gγ 1 knockout results in progressive photoreceptor loss. Even before degeneration begins, affected rods sustain a >90% loss of other transducin subunits: Gα t and Gβ 1 .…”
mentioning
confidence: 84%
“…The Gγ 1 knockout and Gβ 1 heterozygous mice were licensed from Deltagen and the former was characterized previously (10). Details on other animal strains, antibodies, immunoblotting, histological techniques, and immunohistochemical procedures are available in SI Materials and Methods.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We should note that previous studies with rhodopsin and transducin had indicated that high concentrations of rhodopsin might activate transducin in the absence of G␤␥, and that G␤ 1 or G␥ 1 knock-out mice still had some light response (35)(36)(37)(38)(39)(40). Thus, GPCRs possess the ability to catalyze the nucleotide exchange on G␣ subunits.…”
Section: Activation Of Purified G␣ S Mutants By Purified ␤-Adrenergicmentioning
confidence: 96%
“…where S þ ðFÞ is the number of all positive relations, and S À ðFÞ is all negative relations in matrix U(F) [61]. Thus, J(F) characterizes the ratio between the number of all positive and all negative relations.…”
Section: Jðfþ ¼ S þ ðFþ S à ðFþ ð6þmentioning
confidence: 99%